Structure and Properties of SWCNT-Modified CFRP; IOP Conference Series: Materials Science and Engineering; Vol. 731 : Advanced Materials for Engineering and Medicine (AMEM-2019) - Burkov M. V. Mikhail Vladimirovich (2020, 2020)
Title screen